Comparison of Bupivacaine with and without Dexmedetomidine on Duration of Analgesia among Patients Undergoing Cesarean Section Under Spinal Anesthesia: Bupivacaine and Dexmedetomidine: Cesarean Section Under Spinal Anesthesia - Abbas, Shahzadi Erum; Qayyum, Amina; Qamar, Kiran; Tahzeeb, Saiyyadah; Javed, Kamran; Tariq, Hira (Pakistan Journal of Health Sciences, 2025)
Spinal anesthesia is commonly used for cesarean sections. Adjuvants like dexmedetomidine are used to prolong anesthesia effects, reduce postoperative analgesic requirements, and enhance patient comfort. Preemptive analgesia, the administration of analgesics before painful stimuli, can further improve outcomes. While dexmedetomidine is known to enhance postoperative analgesia, existing literature primarily focuses on cesarean sections, with limited local evidence available. Objectives: To compare bupivacaine and dexmedetomidine on analgesia duration among patients having cesarean section under spinal anesthesia. Methods: The quasi-experimental research carried out in the department of Anesthesia of Jinnah Hospital involved 54 women who could be offered cesarean section and were divided into two equal groups (Group B and Group B+D): the former received 10 mg bupivacaine, and the latter 10 mg bupivacaine with the administration of 5 mcg dexmedetomidine intrathecally. Postoperative scores of the pain were measured in the Visual Analogue Scale (VAS). They had rescue analgesia (diclofenac sodium 75 mg) at VAS 3 or above. Vomiting, hypotension, and tachycardia were assessed as complications. SPSS version 25.0 was used in data analysis. Results: Pain scores at all-time points were significantly lower in the dexmedetomidine group (p<0.05). Time to first rescue analgesia was also longer in Group B+D. Conclusions: Adding dexmedetomidine to bupivacaine in spinal anesthesia significantly prolongs analgesia duration and reduces postoperative pain. It is a viable and effective adjuvant for cesarean sections.